Increasing Mathematics Achievement of Senior Secondary School Students through Differentiated Instruction - Adeneye O. A. Awofala; Abisola O. Lawani (Journal of Educational Sciences, 2020)
This study examined the effect of differentiated instruction on senior secondary school students’ achievement in mathematics in Nigeria within the blueprint of the pre-test, post-test non-equivalent control group quasi-experimental research design. The sample comprised 220 students in which three research questions and three null hypotheses guided the study. The experimental group was taught with the differentiated instruction while the control group received instruction with the conventional teaching method for eight weeks. Three valid and reliable instruments, Mathematics Achievement Test (KR-20=0.89), Felder-Soloman Index of Learning Styles (Cronbach α=0.92), and McKenzie Multiple Intelligences Inventory (Cronbach α=0.90), were used for data collection. Results revealed that students in the differentiated instruction group performed significantly better than students in the conventional teaching method group. Also, male students performed slightly better than female students with differentiated instruction, although no significant difference existed between the achievement of male and female students taught mathematics using differentiated instruction. There was no significant main effect of gender on students’ achievement in mathematics. Also, there was no significant interaction effect of treatment and gender on students’ achievement in mathematics. The differentiated instruction made lesson more fascinating, stress-free and created co-operation among students. It was thus, recommended that differentiated instruction be adopted by mathematics teachers in teaching mathematics at the senior secondary school level in Nigeria.